Pengaruh Penerapan Keterampilan Proses dalam Pembelajaran Matematika terhadap Hasil Belajar - Rachmayanti, Diana Nur; Halidjah, Siti; Pranata, Rio (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2024)
This study aims to analyze the influence of the aplication of process skills in mathematical learning on the learning outcomes of 4th grade students of Primary School Negeri 31 Pontianak Utara. The method used in this study is an experimental method with quasi experimental design with nonequivalent control group design. The sample in the study was grade IV A and grade IV B students, each class numbering 19 students. The data collection technique on this study uses measurement techniques and the data collection tool used is a written test in the form of a description. Based on the data analysis, the average post-test experimental class was 79.58 and the control class was 54. From the results of testing the hypothesis using the formula polled variance obtained thitung (5,69) < ttable (2,028), this proves that there is a difference in the post-test values of the experimental class and the control class. To analyze how much the application of the process skills approach in mathematical learning affects the learning outcomes, the effect size formula is used, obtained = 1.54 based on the criteria including the high category. Thus, it can be concluded that the application of skills approach in mathematical learning exerts a high influence on students' learning outcomes.